ANNUAL REPORT OF THE DIRECTOR FOR THE YEAR ENDING 31st MARCH 1961 - Kochi, Central Marine Fisheries Research Statio (Indian Journal of Fisheries, 2011)
ANNUAL REPORT OF THE DIRECTOR FOR THEYEAR ENDING 31st MARCH 1961